Early photographs of the greater one-horned rhinoceros (Rhinoceros unicornis) in the wild - Kees Rookmaaker (Pachyderm)
Despite recurrent obstacles in photographing animals in the wild, there are a few early examples. A dead rhinoceros shot in Assam by Wilfred Dakin Speer was photographed in 1862. An image of a living rhinoceros in Nepal was published in the Illustrated London News of 1906. This was followed by black and white photographs taken in 1909 by Victor Brooke of a rhinoceros attacking his elephant in 1911 during the tour of King George V in Nepal, and in 1923 by George Miller Dyott for the Vernay-Faunthorpe expedition of the American Museum of Natural History in New York. Those taken in 1932 by the Swedish photographer Bengt Berg in Jaldapara, West Bengal, are among the best of early attempts in the wild.